Reaching hard-to-reach men through home-based couple HIV testing among pregnant women and their male partners in western Kenya: a qualitative study - Krakowiak, Daisy (BMC Public Health, 2020)
BACKGROUND: Globally only 79% of adults living with HIV (human immunodeficiency virus) know their status and men in sub-Saharan Africa are considered a particularly hard-to-reach population for HIV testing. Home-based HIV couple testing during the antenatal period is a safe and effective method that has been used to test male partners of pregnant women. The goal of this qualitative study was to identify elements that made couple testing successful and describe important characteristics of this home-based intervention from couples’ perspectives. METHODS: Couples who received scheduled home-based couple testing during pregnancy in Kisumu, Kenya, were purposively sampled based on HIV status from January to May 2015. An interviewer administered all of the in-depth interviews and two coders were directly involved in the data analysis and reconciled codes several times in the process. RESULTS: Twenty-one couples were enrolled: 9 concordant HIV-negative couples, 8 HIV discordant couples, 3 HIV concordant HIV-positive couples, and 1 whose concordance status was unknown. Median age at the time of home-based couple testing was 24 and 28 years for women and men, respectively. Median relationship duration was 3 years and couples had a median of two pregnancies. The major themes that emerged were that home-based couple testing 1) removed the female burden of requesting couple testing, 2) overcame logistical barriers associated with clinic-based testing, 3) encouraged participants to overcome their fear of testing and disclosure, 4) provided privacy in the home, and 5) provided quality time with the health advisors. Importantly, some women appreciated individual testing at the clinic before couple testing and some couples preferred skilled, anonymous health advisors delivering the intervention rather than known community health workers. CONCLUSIONS: The results of this qualitative study suggest that home-based couple testing during pregnancy overcame many of the barriers that limit men’s access to and uptake of clinic-based testing. It encouraged participants to overcome their fear of testing and disclosure through a setting that afforded privacy and quality time with skilled health advisors. These qualitative results may help design effective partner and couple HIV testing programs in the antenatal setting and alongside or within other assisted partner notification services. TRIAL REGISTRATION: Clinicaltrials.gov registry: NCT01784783. Registered prospectively on June 15, 2012.